The management of enteroatmospheric fistula development after bridectomy associated with appendectomy - GÜRKAN, AYSEL (My University, 2022)
Abdominal cerrahinin korkulan bir komplikasyonu olan entero-atmosferik fistül, açık karın yönetimindeki gelişmelere rağmen ciddi mortalite oranına sahiptir. Entero-atmosferik fistüllü hastanın yönetimi, deneyimli cerrahlar ile uzman hemşirelerin yer aldığı multidisipliner bir yaklaşımı ve çok yönlü tedaviyi gerektirir. Bu makale Grade 4 açık abdomenli hastada, vakum yardımlı kapama tedavisi ile kombine edilen bebek biberon emziği tekniğini bireye özgü modifiye ettiğimiz yöntemi sunma amacıyla yazılmıştır.

Enteroatmospheric fistula, which is a fearsome complication of abdominal surgery, has a high rate of mortality despite the developments in open abdomen management. Management of a patient with enteroatmospheric fistula requires a multidisciplinary approach and a multifaceted treatment from a team of experienced surgeons and expert nurses. This article was written in order to present nursing bottle teat technique combined with vacuum-assisted closure treatment with a modified method specific to the individual in a Grade 4 patient with open abdomen.
Apendektomiye bağlı bridektomi sonrası gelişen enteroatmosferik fistülün yönetimi
Keywords: Sağlık Bilimleri; Hemşirelik; Health Sciences; Nursing; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Yoğun Bakım Hemşireliği; Tıbbi ve Cerrahi Hemşirelik; Farmakoloji (hemşirelik); Annelik ve Ebelik; Onkoloji (hemşirelik); Hemşirelik (çeşitli); İleri ve Uzman Hemşirelik; Asistan Hemşirelik; LPN ve LVN; Genel Hemşirelik; Acil Tıp Hemşireliği; Critical Care Nursing; Medical and Surgical Nursing; Pharmacology (nursing); Maternity and Midwifery; Oncology (nursing); Nursing (miscellaneous); Advanced and Specialized Nursing; Nurse Assisting; LPN and LVN; General Nursing; Emergency Nursing; Open abdomen; fistula; vacuumassisted closure; Açık karın; fistül; vakum-yardımlı kapatma